Investigation Of The Critical Features Affecting The Condition Of Oil And Gas Pipeline - Md Arif, Muhammad Nafiz Izzat (IRC, 2016)
Throughout decades the functionality of pipelines has varied and used in many different fields. One of the functions being the transportation of oil and gas from one place to another. To transport such highly volatile and dangerous substances, it is critical to determine the features affecting the integrity of oil and gas pipelines in order to preserve the safety of the society while maintaining the well-being of the environment. In recent years, companies have diverted their focus on oil and gas fields located in deep and ultra-deep waters mainly due to the hydrocarbon reserves in these depths. Therefore, in this project we go deep into the analytical understanding and design in evaluating its major factors which is the external hydrostatic pressure that affect the pipelines and the effects by using different steel grade (X56, X60, X65 and X70) at different water depth ranging from 800m, 1400m, 2000m to 3500m.